Spatial Data Usability - Monica Wachowicz; Gary Hunter (Data Science Journal, 2003)
Almost 150 years ago a London doctor combined maps of cholera deaths and water pumps to discover the source of a deadly epidemic, and the case has since become an acclaimed use of spatial analysis taught to generations of geography students worldwide. Moving forward to the present day, data mining techniques are now radically changing the way supermarkets think about product placement within their stores, and telephone customers are moving away from their traditional “YellowPages” directories and turning instead to enhanced “YellowMap” products. While these are all very positive examples, on the other hand a recent UK government hearing into the establishment of an underground radioactive waste repository determined not to proceed with this major project after the results of groundwater hydrology modelling were rejected because they could not be validated.